The Effects of Covid-19 on Students’ Learning Process - Ahmad Siraj Julian (English LAnguage Study and TEaching, 2021)
This research aims to examine the effect of Covid-19 on students’learning process related to personal factors, teachers’ involvementfactor as well as parents’ involvement factor. This study used descriptive qualitative methods for data collection. The population was the grade IX students at Madrasah Tsanawiyah Negeri 3 Aceh Besar. The sample in this study was 30 students of class IX Madrasah Tsanawiyah Negeri 3 Aceh Besar. There were 9 male and 21 female. The writer used questionnaire as the research instrument in collecting the data.Meanwhile, in analysing the obtained data, the writer used percentage formula. The results of this study indicated that most students got negative effects when studying online, such became lazier, did not feel to have enough teacher’s involvement and not enough parentds’ support.